Increasing the Growth and Development of Chili-Pepper Under Three Different Shading Condition in Response to Biofertilizers Application - Didik Hariyono; Fandyka Yufriza Ali; Agung Nugroho (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2021)
Biological agents such as rhizosphere bacteria and Vesicular Arbuscular Mycorrhiza (VAM) are potential agents to improve soil qualities. In addition, species and varieties of crops give different response to the shading related to their growth and development. The research aimed to determine the effect of biofertilizer application under different levels of shading conditions on the growth and capsaicin content of Capsicum frutescens L. and evaluate the suitable levels of shading. The research was conducted from February to June 2019 at Universitas Brawijaya. Bhaskara variety was chosen in this research. Thirteen treatments and three replications were arranged in the randomized design with nest pattern (Nested). The treatments were a combination between the shading level and biofertilizers. The dry weight, nutrient content, fresh weight and capsaicin content were observed. The results showed the application of biofertilizers consisted of PGPR and VAM consortium, under the lowest shading condition (25%) increased the total dry weight of chili, the nutrients absorption, and the capsaicin content. The capsaicin content is influenced by the fruit weight of chili and plant nitrogen uptake. Biofertilizers and the lowest shading conditions contribute to supporting the growth and development of chili pepper.